A Pilot Study of Multiplex Ligation-Dependent Probe Amplification Evaluation of Copy Number Variations in Romanian Children with Congenital Heart Defects - Bolunduț, Alexandru Cristian; Nazarie, Florina; Lazea, Cecilia; Șufană, Crina; Miclea, Diana; Lazăr, Călin; Mihu, Carmen Mihaela (Genes, 2024)
Congenital heart defects (CHDs) have had an increasing prevalence over the last decades, being one of the most common congenital defects. Their etiopathogenesis is multifactorial in origin. About 10–15% of all CHD can be attributed to copy number variations (CNVs), a type of submicroscopic structural genetic alterations. The aim of this study was to evaluate the involvement of CNVs in the development of congenital heart defects. We performed a cohort study investigating the presence of CNVs in the 22q11.2 region and GATA4, TBX5, NKX2-5, BMP4, and CRELD1 genes in patients with syndromic and isolated CHDs. A total of 56 patients were included in the study, half of them (28 subjects) being classified as syndromic. The most common heart defect in our study population was ventricular septal defect (VSD) at 39.28%. There were no statistically significant differences between the two groups in terms of CHD-type distribution, demographical, and clinical features, with the exceptions of birth length, weight, and length at the time of blood sampling, that were significantly lower in the syndromic group. Through multiplex ligation-dependent probe amplification (MLPA) analysis, we found two heterozygous deletions in the 22q11.2 region, both in patients from the syndromic group. No CNVs involving GATA4, NKX2-5, TBX5, BMP4, and CRELD1 genes were identified in our study. We conclude that the MLPA assay may be used as a first genetic test in patients with syndromic CHD and that the 22q11.2 region may be included in the panels used for screening these patients.